2014
DOI: 10.1590/1809-4503201400050011
|View full text |Cite
|
Sign up to set email alerts
|

Bullying and associated factors among Brazilian adolescents: analysis of the National Adolescent School-based Health Survey (PeNSE 2012)

Abstract: ABSTRACT:Objective: To estimate the prevalence of bullying from the victim's perspective in Brazilian school children and to analyze its association with individual and family context variables. Methods: An analysis of the data on 109,104 adolescents, obtained by the National Adolescent School-based Health Survey, held in schools in 2012, was carried out. An association model between bullying and explanatory variables was tested in different contexts: sociodemographic, risk behaviors, mental health and family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0
18

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 29 publications
3
28
0
18
Order By: Relevance
“…Despite not including specific questions about this issue, the findings of the VIVA survey were consistent with those of other studies that showed that violence against school children in the form of threats and the use of fear particularly affects younger adolescents 31,32 It is also important to note the fact that victims sought treatment at urgent and emergency care centers, probably suggesting that they were victims of more serious violent events resulting in injury, thus demonstrating that tackling violence at school should be a priority.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Despite not including specific questions about this issue, the findings of the VIVA survey were consistent with those of other studies that showed that violence against school children in the form of threats and the use of fear particularly affects younger adolescents 31,32 It is also important to note the fact that victims sought treatment at urgent and emergency care centers, probably suggesting that they were victims of more serious violent events resulting in injury, thus demonstrating that tackling violence at school should be a priority.…”
Section: Discussionsupporting
confidence: 85%
“…Bullying consists of threats and insults made by friends or classmates, but can also involve the use of physical force 32 . This problem has been studied by surveys of adolescents, such as the National School Health Survey (Pesquisa Nacional de Saúde do Escolar -PeNSE) 31,32 . Studies have shown that there is a significant association between violence experienced by adolescents and involvement in acts of violence at school, either as victims or perpetrators 33 .…”
Section: Discussionmentioning
confidence: 99%
“…However, these parental practices are incompatible with what one would expect of mothers with more years of schooling. On the other hand, parental supervision seems to protect children from bullying, as has been reported in the literature 14 .…”
Section: Discussionmentioning
confidence: 68%
“…In Brazil, the first two PeNSEs (National School Health Survey) found increasing rates of involvement in bullying among the students; 5.4% of students in state capitals reported having been bullied in 2009, and 7.2% in 2012 [13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…Unlike other types of violence, there is no incitement from the victim's side. 2 In recent years, peer-peer bullying in the school setting has become increasingly prominent due to its escalation and negative impact on the health status of affected children, [3][4][5][6][7][8] and has transcended the school sphere to become a major public health problem. 3,4 One of the factors that contributes to its importance is that referred to as "code of silence" by Ortega.…”
Section: Introductionmentioning
confidence: 99%